Repercussão da avaliação de desempenho do profissional técnico da educação superior sob a perspectiva de avaliadores e avaliados - Ferri, Silvania da Silva (2020)
Evaluating people's performance has been a great challenge for organizations, due to the complexity of proceeding with the evaluation process in such a way that it will be fair to the ones involved and it is also used to achieve the organization's development goals. This work aims to analyze the performance evaluation process of the Technical Professionals of Higher Education – PTES at UNEMAT, under the perspective of evaluated and evaluators’. It presents theoretical aspects about people management in organizations, highlighting the performance evaluation process and the reference of some models. Discusses some research carried out on performance evaluation in Public Administration and its importance for the institution. It is a descriptive research with a qualitative approach, and as for technical procedures, it is classified as a case study whose sources were documentary and field research. The data collection instrument was the questionnaire sent to all the 198 servers Higher Education Technical Professionals (PTES) and Teacher assigned to the administrative unit - Rectory of UNEMAT. We had some analyzed from 48 participants, 26 of them being PTES servers and 22 being managers; representing the managers, there were 16 technical and 6 teacher. The analysis consisted of categorizing information to understand the problem using the Content Analysis technique, according to Bardin (2016). As a result, both evaluated and evaluators agree that the criteria of behavior at work, quality at work, initiative, efficiency and responsibility, do not contemplate the degree of specificity and responsibility that the function requires, mainly by using a standard performance evaluation form for all PTES servers, not contemplating criteria necessary for the evaluation of managers. Regarding the evaluation procedures, concerns were observed with the low number of PTES servers in the institution, lack of impersonality in the evaluations, lack of training for the evaluation process and lack of feedback. When it comes to the perception of the results of the performance evaluation as an improvement for the performance, the results obtained by the research indicate that the participants are unaware of any action developed in the institution that is related to the improvement in the performance of the server and consequent organizational development.